Exploring Differences in Speech Processing Among Older Hearing-Impaired Listeners With or Without Hearing Aid Experience: Eye-Tracking and fMRI Measurements - Habicht, Julia; Behler, Oliver; Kollmeier, Birger; Neher, Tobias (Frontiers in Neuroscience, 2019)
Recently, evidence has been accumulating that untreated hearing loss can lead to neurophysiological changes that affect speech-in-noise processing abilities. In order to shed more light on how aiding may impact these effects, this study explored the influence of hearing aid (HA) experience on the cognitive processes underlying speech comprehension. Eye-tracking and functional magnetic resonance imaging (fMRI) measurements were carried out with acoustic sentence-in-noise (SIN) stimuli complemented by pairs of pictures that either correctly (target) or incorrectly (competitor) depicted the sentence meanings. For the eye-tracking measurements, the time taken by the participants to start fixating the target picture (the ‘processing time’) was measured. For the fMRI measurements, brain activation inferred from blood oxygenation level dependent (BOLD) responses following sentence comprehension was measured. A noise-only condition was also included. Groups of older hearing-impaired individuals matched in terms of age, hearing loss and working memory capacity with (eHA; N = 13) or without (iHA; N = 14) HA experience participated. All acoustic stimuli were presented via earphones with individual linear amplification to ensure audibility. Consistent with previous findings, the iHA group had significantly longer (poorer) processing times than the eHA group, despite no differences in speech recognition performance. Concerning the fMRI measurements, there were indications of less brain activation in some right frontal areas for SIN relative to noise-only stimuli in the eHA group compared to the iHA group. Together, these results imply that HA experience leads to faster speech-in-noise processing, possibly related to less recruitment of brain regions outside the core sentence-comprehension network. Follow-up research is needed to substantiate these initial findings regarding changes in cortical speech processing with HA use.